2020
DOI: 10.1017/jfm.2020.600
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of stratified horizontal shear flows at low Péclet number

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…They are now tested using direct numerical simulations devoted to the stellar regime (Prat & Lignières 2013Garaud et al 2017;Prat et al 2016;Gagnier & Garaud 2018;Kulenthirarajah & Garaud 2018). The horizontal turbulence induced by horizontal gradients of the differential rotation has only been examined in the stellar regime in a few works, which again use phenomenological arguments (Zahn 1992;Maeder 2003), results from lab experiments studying differentially rotating flows (Richard & Zahn 1999;), and first devoted numerical simulations (Cope et al 2020). The systematic study of the combined effect of stable stratification, rotation, and thermal diffusion in the stellar context has only been recently undertaken.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are now tested using direct numerical simulations devoted to the stellar regime (Prat & Lignières 2013Garaud et al 2017;Prat et al 2016;Gagnier & Garaud 2018;Kulenthirarajah & Garaud 2018). The horizontal turbulence induced by horizontal gradients of the differential rotation has only been examined in the stellar regime in a few works, which again use phenomenological arguments (Zahn 1992;Maeder 2003), results from lab experiments studying differentially rotating flows (Richard & Zahn 1999;), and first devoted numerical simulations (Cope et al 2020). The systematic study of the combined effect of stable stratification, rotation, and thermal diffusion in the stellar context has only been recently undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of the turbulence generated by horizontal shears has been recently explored in the nonrotating case by Cope et al (2020) and Garaud (2020). They find when exploring the parameter space using Direct Numerical Simulations (DNS) a turbulent stratified regime where the turbulent transport can be modeled by an eddy diffusivity.…”
mentioning
confidence: 99%
“…This corresponds to an anti-diffusive transport of angular momentum. Cope et al (2020) and Garaud (2020) estimated the vertical turbulent diffusion coefficient associated with the horizontal shear instability using scaling laws but they did not provide any proof that the transport of chemical elements is indeed diffusive. In addition, they did not discuss the transport of angular momentum.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the horizontal diffusion coefficient, since the inital model of Zahn (1992) that was based on phenomenological arguments, other models based on energetic arguments (Maeder 2003) or results of an unstratified Taylor-Couette experiment ) have been proposed, but this coefficient is still poorly constrained, and its impact on stellar evolution is clearly overlooked. The first numerical simulations of the turbulent transport triggered by the instabilities of a horizontal shear in stellar conditions have also been performed (Cope et al 2020;Garaud 2020). Finally, Park et al (2020Park et al ( , 2021 studied the linear instabilities of the horizontal differential rotation in stellar radiation zones as a function of stratification, rotation, and thermal diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, much more work remains to be done before one can gain a complete understanding of shear instabilities and GSF instabilities in stars. In particular, the present study was limited to the equatorial region of a star, and the dynamics away from the equator are known to be substantially different, both for the GSF instability (Knobloch & Spruit 1982;Barker et al 2020), and for the shear instability (Cope et al 2020;Garaud 2020b). In the former case, Barker et al (2020) found that the GSF instability criterion is relaxed compared with (5), and that angular momentum layering can lead to a vast increase in the turbulent transport coefficient.…”
Section: Summary and Discussionmentioning
confidence: 99%